Investigation of the Resistance of Klebsiella Bacteria to Antibiotics and the Synthesis of Virulence Factors Isolated from Various Pathogenic Infections - Ali, Farah (Journal La Lifesci, 2024)
The purpose of the study is to establish the level of antibiotic resistance in Klebsiella pneumoniae and to evaluate the production of virulence factors of the isolates originating from patients with diverse infections in Baghdad. In this study,75 clinical samples, including 32 samples of wounds, fifteen burn samples, 17 sputum samples and eleven samples of urine were collected from patients afflicted with different infections from some hospitals in Baghdad city, during the period from October to March 2023. It was found that 22 of the isolates were of Klebsiella pneumonia isolates after culturing the clinical samples on MacConkey agar, blood agar, and Eosin methylene blue medium, in addition to studying the morphologic appearance, biochemical tests, and confirmation of diagnosis using the VITEKA2 system. The antibiotic sensitivity test showed that all isolates showed (100%) multi-drug resistance to 7 antibiotics including Cefotaxime, Ampicillin, Chloramphenicol, Gentamicin, Rifampicin, while most of the isolates were sensitive to Azithromycin. The investigation of certain virulence factors of the Klebsiella pneumonia bacteria revealed that all of the isolates were encased in a capsule and were incapable of producing the hemolysin enzyme, but they were all able to produce the urease enzyme and form biofilm. The isolates produced bacteriocin at a rate of 12%.